The impact of total quality management and employees' job satisfaction at Mahkota Medical Centre, Melaka / Siti Asma Abdul Jamal - Abdul Jamal, Siti Asma (Faculty of Business and Management, 2009)
The purpose of this research is to examine the perception of Total Quality Management (TQM) and its impact on job satisfaction within employees' of Mahkota Medical Centre (MMC). My research is conduct to determine the relationship between Total Quality Management (TQM) and MMC's employees' job satisfaction. The five TQM components that the researcher chooses in this research are organizational trust, customer focus, rewards and recognition, teamwork, and organizational culture. I want to identify whether there is a relationship between TQM and level of employees' job satisfaction at MMC. The researcher chooses to use descriptive research design as research method and the researcher use survey in order to collect the data. Data used in this research are primary data and so on secondary data such as journal and articles. The researcher also use structured questionnaire design to obtain the data in order to convenience the respondent to give feedback because most of them busy with their work. The sample size in this research is 50 respondents of MMC's employees' itself. From the result, researcher found that the most important of TQM component that affect employees' job satisfaction is organizational culture, followed by organizational trust, rewards and recognition, teamwork and the less important is customer focus.